2016
DOI: 10.1080/15548627.2015.1124225
|View full text |Cite
|
Sign up to set email alerts
|

BAG3 regulates total MAP1LC3B protein levels through a translational but not transcriptional mechanism

Abstract: Autophagy is mainly regulated by post-translational and lipid modifications of ATG proteins. In some scenarios, the induction of autophagy is accompanied by increased levels of certain ATG mRNAs such as MAP1LC3B/LC3B, ATG5 or ATG12. However, little is known about the regulation of ATG protein synthesis at the translational level. The cochaperone of the HSP70 system BAG3 (BCL2-associated athanogene 3) has been associated to LC3B lipidation through an unknown mechanism. In the present work, we studied how BAG3 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…A recent report in the literature has shown that BAG3 actually regulates the basal amount of total cellular LC3B by controlling its mRNA translation. This was specific for LC3, since no other ATG proteins were found to be affected in that study (Rodríguez et al, 2016). We have observed, however, decreased Atg5 protein levels in siBAG3-transfected TM cells.…”
Section: Autophagy and Mechanical Stretch: Dual Role In Repair Andmentioning
confidence: 67%
“…A recent report in the literature has shown that BAG3 actually regulates the basal amount of total cellular LC3B by controlling its mRNA translation. This was specific for LC3, since no other ATG proteins were found to be affected in that study (Rodríguez et al, 2016). We have observed, however, decreased Atg5 protein levels in siBAG3-transfected TM cells.…”
Section: Autophagy and Mechanical Stretch: Dual Role In Repair Andmentioning
confidence: 67%
“…Evidently, BAG3 facilitates the clearance of damaged Tom20 and its down regulation increases the level of Parkin translocation to the mitochondria after CCCP treatment. It was previously reported that BAG3 knock-down increased the amount of mitochondria in HeLa cells (Rodríguez et al, 2016). The accumulation of dysfunctional mitochondria within cells has been implicated in the development of neurodegenerative disorders such as Parkinson's disease.…”
Section: Discussionmentioning
confidence: 97%
“…Recent studies have demonstrated enhanced expression of BAG3 and increased levels of its chaperonic activity along with heat shock proteins during cellular stress and aging, suggesting a crucial role for BAG3 in determining the cellular stress response (Behl et al, 2011). BAG3 is known to play an important role in intracellular protein homeostasis by participating either in protein folding and/or clearance of damaged proteins (Rodriguez et al, 2016). To this end, BAG3 functions along with other proteins such as SQSTM1/P62 (referred to as P62 from here on), HSP70, and LC3 in a process called macroautophagy in which misfolded or damaged proteins and organelles are sequestered within autophagosomes and targeted to lysosomes for degradation (Behl et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies, as well as increasing evidence, support this postulation as BIS has been shown to regulate several proteins, including microtubule-associated protein 1 light chain 3β (MAP1LC3B) [32], STAT3 [16], and myosin heavy chain [33]. …”
Section: Discussionmentioning
confidence: 99%